Faktor yang Berperan Sebagai Prediktor Kematian pada Pasien Non-ST Elevation Infarction (NSTEMI) pada 48 Jam Pertama Perawatan - Linda Widyarani; Muhammad Rasjad Indra; Tony Suharsono (Jurnal Keperawatan Notokusumo, 2014)
Background: In-hospital mortality rate NSTEMI equally even higher than STEMI. In dr. Soedono Madiun general hospital, in-hospital mortality rate of NSTEMI was 17% in 2012 and had escalated reached 21% in 2013. Among patients NSTEMI with late arrival (>2 hours) and arrhythmias had a higher in-hospital mortality rate. Objective: To determine the factors that had a role as early predictor of in-hospital mortality in NSTEMI patient. Method: This research had been conducted in dr. Soedono Madiun general hospital. This research use quantitative research method, use approach of observational analytic with longitudinal prospective design. This research had been done in April until June, 2014 with the number of samples is 50 people. Analysis of data use multivariate analysis regression logistics. The collecting data obtained by observation and an interview. Result: The mean of delay time was 7,89±6,44 hours. Self-medication (0,000) and health-care seeking pattern (0,002) were factors influencing pre hospital delay among patients NSTEMI >2 hours. Analysis of bivariate showed that pre hospital delay statistically significant predictor of in-hospital mortality (0,001). Among patients NSTEMI with late arrival (>2 hours) had a higher in-hospital mortality rate. The number of patients who arrive at the hospital early was 13 people and at the hospital late only 2 people. After analysis of multivariate, regression logistic showed that systolic blood pressure ?90 mmHg (p=0,023, RR=7,596, ?=0,05) and arrhythmias (p=0,047, RR=6,866, ?=0,05) proven a role as early predictor of in-hospital mortality in NSTEMI patient. Frequently, total AV block proven a role as early predictor of in-hospital mortality of NSTEMI. Conclusion: The strongest factor had a role as early predictor of in-hospital mortality in NSTEMI patient is systolic blood pressure ?90 mmHg.